Acoustics and activity noise in school classrooms in Finland. (15th December 2016) - Sala, Eeva; Rantala, Leena
Abstract: School classrooms are learning spaces for children and workplaces where a teacher's most important tool, his or her voice, is subjected to considerable loading. Because noise has several detrimental effects on human functioning including speech production and perception, a noiseless environment and good acoustics in classrooms are important. The main aim of this study was to investigate the classroom as a sound environment and to ascertain the effect of acoustics. Activity noise levels, background noise levels and acoustics were measured in school classrooms (N = 40), and the associations between these were studied. The acoustics of measured in these classrooms were compared to the values of the Finnish national standard. Acoustic parameters (reverberation time and Speech Transmission Index, STI) and background noise levels were measured in unoccupied classrooms and activity noise levels were measured during classroom instruction. The results showed that only few classrooms fulfilled the acoustic criteria of the Finnish national standard and no classroom fulfilled the criterion for acoustics measured according to the STI. In most of the classrooms the background noise level was higher than recommended and activity noise levels were high for listening and communication. According to the results, the acoustic environment in these school classrooms was detrimental to speech communication and learning. This also implies a risk of occupational voice disorders. Acoustic ergonomics should be taken into account and acoustic standards should to be fulfilled when new schools are built and old ones refurbished.